2012
DOI: 10.4103/0253-7613.96321
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of intrathecal midazolam and low dose clonidine: Efficacy, safety and duration of analgesia. A randomized, double blind, prospective clinical trial

Abstract: Background:The study was planned to assess the comparative efficacy, safety and duration of analgesia produced by low-dose clonidine and midazolam when used as adjuvant for spinal anesthesia.Materials and Methods:This is a randomized, participant and observer blind, prospective, parallel group clinical trial. Fifty ASA grade I and II patients posted for lower abdominal surgery were randomly allocated into two groups. BC group received spinal clonidine 30 μg and BM group received preservative-free midazolam 2 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
8
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
5
8
1
Order By: Relevance
“…22 Another study, comparing intrathecal midazolam with clonidine, reported that 2 mg intrathecal midazolam provided superior analgesia than 30 μg clonidine with fewer adverse effects in patients undergoing lower abdominal surgeries. 23 Intrathecal midazolam did not affect the duration of motor blockade in the present study. Although a few studies have reported prolongation of motor blockade after intrathecal midazolam, 12,14 a meta-analysis aiming to evaluate the effectiveness and side-effects of intrathecal midazolam in the perioperative setting reported that intrathecal midazolam did not affect the duration of motor blockade.…”
Section: Discussioncontrasting
confidence: 50%
“…22 Another study, comparing intrathecal midazolam with clonidine, reported that 2 mg intrathecal midazolam provided superior analgesia than 30 μg clonidine with fewer adverse effects in patients undergoing lower abdominal surgeries. 23 Intrathecal midazolam did not affect the duration of motor blockade in the present study. Although a few studies have reported prolongation of motor blockade after intrathecal midazolam, 12,14 a meta-analysis aiming to evaluate the effectiveness and side-effects of intrathecal midazolam in the perioperative setting reported that intrathecal midazolam did not affect the duration of motor blockade.…”
Section: Discussioncontrasting
confidence: 50%
“…Similar observations have been reported by other studies (33,34). Further investigations have shown that the addition of midazolam or fentanyl to intrathecal bupivacaine does not alter the peak level of the sensory block (9,35,36). Similar observations were noted in our study.…”
Section: Discussionsupporting
confidence: 93%
“…Intrathecal use of low dose clonidine and fentanyl as adjuvant to bupivacaine has not been shown to be associated with respiratory depression in literature. [26][27][28][29][30][31][32] Thus, the findings in this present study indicated a safe ventilatory profile of both drugs which did not end up in a respiratory depression and is consistent with the findings reported in literature. Although a few case reports describes respiratory depression after intrathecal fentanyl (after 100 mcg of epidural fentanyl) yet its use in low-dosage as an adjuvant to bupivacaine is relatively safe and rarely ends up in respiratory depression.…”
Section: Discussionsupporting
confidence: 90%